Hurdle Rate and Adverse Selection on Escalation of Commitment - M. Arsyadi Ridha (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This article tests the effect of hurdle rates and adverse selection on escalation of commitment. Participants consist of 135 junior managers who had passed two course of management. The result indicates that the managers with adverse selection conditions will tend not to continue unfavorable projects. This research also affirms that the managers with adverse selection conditions will be more likely not to continue projects that are not favorable under the conditions of self-set hurdle rates compared to the conditions of organization-set hurdle rates. This article may contribute to empirical evidence of a decline in comprehensive escalation of commitments.Â Keywords: adverse selection, self-set hurdle rates, organization-set hurdle rates, escalationÂ of commitment